Qualitative Study: Comparison of Implementation of Independent Curriculum in Early Childhood Institutions in Sukoharjo District - Bambang Winarji; Upik Elok Endang Rasmani; Siti Wahyuningsih; Novita Eka Nurjanah; Jumiatmoko Jumiatmoko; Nurul Shofiatin Zuhro; Anjar Fitrianingtyas (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to compare the implementation of the independent curriculum of two institutions in Sukoharjo District, namely TK Teladan and RA STIBA AZKIYAA. The study used a descriptive research approach to analyze the implementation of the independent curriculum at Teladan Kindergarten. Data was collected through observation, interview, and documentation techniques. This research was conducted for 3 months and used the principal and accompanying teacher of class B2 of Teladan Kindergarten and RA STIBA AZKIYA as research informants. The differences researchers found in implementing the independent curriculum in TK Teladan show the full utilization of the independent curriculum. In contrast, RA Stiba Azkiya is still in the process of fully implementing the curriculum.Â The findings suggest that Teladan Kindergarten's approach, which supports active learning, is highly effective in allowing children to explore and develop discipline and responsibility. However, RA Stiba Azkiya needs further time and support to implement the independent curriculum fully. Evaluations differ, with TK Teladan evaluating after each lesson and RA Stiba Azkiya reporting every 3 to 6 months. Both institutions recommended providing more intensive training and support to teachers to improve the implementation of the self-directed curriculum.